Penerapan Projek Penguatan Profil Pelajar Pancasila Tema Kewirausahaan untuk Meningkatkan Minat Berwirausaha Siswa Sekolah Dasar - Acep Iyan; Adinda Dyah Permata; Fadilah Putri Awaliah; Salsha Fairuz Putri Isa; Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The Pancasila Student Profile Strengthening Project (P5) is an educational initiative that aims to introduce the concept of entrepreneurship to students by exploring the concept of creativity and waste utilization in entrepreneurship. This article aims to fill the knowledge gap and contribute to the understanding of how P5 can effectively increase the entrepreneurial interest of primary school students, Data sources in this study are taken from secondary data sources in the form of research journals, activity documents, activity schedules, and so on. The data that has been obtained is then tested for data credibility, using source triangulation techniques, or checking data through several sources so that saturated and true data is obtained. The results showed that P5 was significantly able to foster entrepreneurial spirit in students. The introduction of the concept of entrepreneurship at an early age is considered crucial in increasing interest in entrepreneurship in the future. Parental involvement and community support play a key role in shaping positive attitudes towards entrepreneurship. The application of P5, especially with a focus on Entrepreneurship Education, is considered a comprehensive learning model to shape entrepreneurial character and skills at primary school level